Beyond the gene - Sapp, Jan (Monographs on the History and Philosophy of Biology, 1987)
The scope and significance of cytoplasmic inheritance has been the subject of one of the longest controversies in the history of genetics. In the first major book on the history of this subject, Jan Sapp analyses the persistent attempts of investigators of non-Mendelian inheritance to establish their claims, in the face of strong resistance from nucleo-centric geneticists and classical neo-Darwinians. A new perspective on the history of genetics is offered, as he explores the oppositions which have shaped theoretical thinking about heredity and evolution throughout the century: materialism/vitalism, reductionism/holism, preformation/epigenesis, neo-Darwinism/neo-Lamarckism, gradualism/saltationism.